A sensorless, physiologic feedback control strategy to increase vascular pulsatility for rotary blood pumps. (May 2023) - Tan, Zhehuan; Huo, Mingming; Qin, Kairong; El-Baz, Ayman S.; Sethu, Palaniappan; Wang, Yu; Giridharan, Guruprasad A.
Highlights: A control system to enhance vascular pulsatility for rotary blood pump was proposed. Switching two differential pump speed setpoints to raise vascular pulsatility. The proposed control algorithm was only based on intrinsic pump speed measurements. This algorithm augmented vascular pulsatility, provided flow rates, avoided suction. Abstract: Continuous flow rotary blood pumps (RBP) operating clinically at constant rotational speeds cannot match cardiac demand during varying physical activities, are susceptible to suction, diminish vascular pulsatility, and have an increased risk of adverse events. A sensorless, physiologic feedback control strategy for RBP was developed to mitigate these limitations. The proposed algorithm used intrinsic pump speed to obtain differential pump speed (Δ RPM ). The proposed gain-scheduled proportional-integral controller, switching of setpoints between a higher pump speed differential setpoint (Δ RPMHr ) and a lower pump speed differential setpoint (Δ RPMLr ), generated pulsatility and physiologic perfusion, while avoiding suction. The switching between Δ RPMHr and Δ RPMLr setpoints occurred when the measured Δ RPM reached the pump differential reference setpoint. In-silico tests were implemented to assess the proposed algorithm during rest, exercise, a rapid 3-fold pulmonary vascular resistance increase, rapid change from exercise to rest, and compared with maintaining a constant pump speed setpoint. The proposed control algorithm augmented aortic pressure pulsatility to over 35 mmHg during rest and around 30 mmHg during exercise. Significantly, ventricular suction was avoided, and adequate cardiac output was maintained under all simulated conditions. The performance of the sensorless algorithm using estimation was similar to the performance of sensor-based method. This study demonstrated that augmentation of vascular pulsatility was feasible while avoiding ventricular suction and providing physiological pump outflows. Augmentation of vascular pulsatility can minimize adverse events that have been associated with diminished pulsatility. Mock circulation and animal studies would be conducted to validate these results.